WHEN HOME ISN’T HOME: MENILIK KEGALAUAN MILENNIAL DAN GEN-Z DI PERANTAUAN - Priono, Agus Budi; Darma, Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
This study aims to determine the effect of the above variables on the motivation of millennial employees and Gen-Z when working away from their homebase. Data analysis in this study was carried out by means of data collection, data reduction, data display and conclusion drawing. Meanwhile, the credibility test uses data triangulation and member check. The results of the study found that millennials and Gen-Z consider the availability of the internet  is important to facilitate their access to social media. They are also shown to be adaptive with other employees of various generations where they have no barriers to communicating with each other. E-leadership is deemed necessary to be implemented in organizations, especially in the current 4.0 era, however they tend to want to be monitored for their work progress every day instead of being given the freedom to complete their tasks. For those who work far from the homebase, they hope to come home every month or every 3 months and the assignment after this is at their homebase.